Antibiotic resistance profiles of enterobacteria isolated from weaned piglets - Barroso, Marlon do Valle (2019)
Pork meat is the most consumed source of animal protein in the world. In order to achieve this high productive efficiency, swine farming has undergone improvements in several sectors. Among these, the supply of antibiotics to improve animal performance and efficiency has been widely discussed, mainly due to the emergence of multiresistant bacteria. This study aimed to evaluate the susceptibility profile of Enterobacteriaceae isolated from feces of weaned piglets and to investigate the distribution of resistance genes and plasmids in the multiresistant isolates. A total of 618 isolates of the Enterobacteriaceae family were obtained from fecal samples fed a control diet without antibiotics (n = 384) or diet containing colistin and tylosin (n = 234). The susceptibility of the isolates against 12 antibiotics was evaluated using the breakpoint technique. From the isolates obtained, 54% (n = 334) showed resistance to at least four antibiotics and were defined as multiresistant. The highest frequencies of resistance were observed for the antibiotics tetracycline (81%), ampicillin (90%) and amoxicillin (85%). Significant differences in the frequency of colistin (P<0.001), cephalexin (P<0.001), kanamycin (P<0.026) and doxycycline (P<0.001) resistance were observed among the bacterial isolates obtained from treatment control + antibiotics when compared to the control. The isolates were grouped based on genotypic fingerprinting (BOX-PCR) and ninety-four isolates with greater number of resistance phenotypes had the 16S rRNA gene sequenced and the distribution of resistance genes assessed by multiplex PCR. Results indicated a close association between the presence of the resistance genes and the resistance phenotype observed in vitro. At least one gene for the extended-spectrum β-lactamases (bla TEM , bla SHV or bla CTX - M ) was found in all genera of enterobacteria analyzed. In addition, it was demonstrated the transfer, through conjugation, of the mcr-1 gene from the isolate Escherichia coli UFV-627 to the E. coli K12 (Nal R , F - ) recipient strain. These results indicate a high frequency of antibiotic resistance among bacterial isolates obtained from feces of weaned piglets that received rations with or without antibiotics, which corroborates the hypothesis that the gastrointestinal tract of piglets represents a potential reservoir of multiresistant enterobacteria. In addition, the results suggest that horizontal transfer mechanisms, such as conjugation and ICEs, between phylogenetically related species, may mediate the spread of these resistance genes in the gastrointestinal tract of these animals. Keywords: Enterobacteria. Antibiotic resistance. Weaned piglets. ESBL genes. mcr-1 and conjugative plasmids